Morphological and Genomic Features of the New Klosneuvirinae Isolate Fadolivirus IHUMI-VV54 - Andreani, Julien; Schulz, Frederik; Di Pinto, Fabrizio; Levasseur, Anthony; Woyke, Tanja; La Scola, Bernard (Frontiers in Microbiology, 2021)
Since the discovery of Mimivirus, viruses with large genomes encoding components of the translation machinery and other cellular processes have been described as belonging to the Nucleo-cytoplasmic large DNA viruses (NCLDV). Recently, genome-resolved metagenomics led to the discovery of more than 40 viruses that have been grouped together in a proposed viral subfamily named Klosneuvirinae. Members of this group had genomes of up to 2.4 Mb in size and featured an expanded array of translation system genes. Yet, despite the large diversity of the Klosneuvirinae in metagenomic data, there are currently only two isolates available. Here, we report on the isolation of a novel giant virus known as Fadolivirus from an Algerian sewage site and provide morphological data throughout its replication cycle in amoeba and a detailed genomic characterisation. The Fadolivirus genome, which is more than 1.5 Mb in size, encodes 1,452 predicted proteins and phylogenetic analyses place this viral isolate as a near relative of the metagenome assembled Klosneuvirus and Indivirus. The genome encodes for 66 tRNAs, 23 aminoacyl-tRNA synthetases and a wide range of transcription factors, surpassing Klosneuvirus and other giant viruses. The Fadolivirus genome also encodes putative vacuolar-type proton pumps with the domains D and A, potentially constituting a virus-derived system for energy generation. The successful isolation of Fadolivirus will enable future hypothesis-driven experimental studies providing deeper insights into the biology of the Klosneuvirinae.